2014
DOI: 10.15302/j-fase-2014040
|View full text |Cite
|
Sign up to set email alerts
|

A microarray study of altered gene expression during melanoblasts migration in normal pigmented White Leghorn and hyperpigmented mutant Silky Fowl

Abstract: Melanoblasts originating from neural crest cells can migrate through the mesenchyme of the developed embryo and give rise to melanocytes. Unlike the melanocytes that are confined to the integument in other vertebrates, melanocytes in Silky Fowl can reach the ventral regions of the embryos owing to differences in gene expression in the process of melanoblasts migration. In this study, we used microarray profiling to identify differences in gene expression between White Leghorn and Silky Fowl. Differential expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…Previous studies have shown that melanocytes in the skin and inner organs of SF are mainly distributed around the blood vessels and mast cells 15 16 . Our previous work also indicated the same characteristic distribution of melanocytes in different SF organs, and we found that the hyperpigmentation plays an important role in immune system development 14 17 . A previous report has demonstrated that the three-week age is very important for the development of B-cells and provides an opportunity for some pathogenic infection 18 .…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that melanocytes in the skin and inner organs of SF are mainly distributed around the blood vessels and mast cells 15 16 . Our previous work also indicated the same characteristic distribution of melanocytes in different SF organs, and we found that the hyperpigmentation plays an important role in immune system development 14 17 . A previous report has demonstrated that the three-week age is very important for the development of B-cells and provides an opportunity for some pathogenic infection 18 .…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, similar results were obtained for immune organ indices and immune gene expressions in the F2 population, which further supports the hypothesis that inhibition of immune organ development is substantially related to the atypical melanocyte migration, rather than variations among different breeds. Our previous microarray study revealed that genes involved in the innate immune response are expressed at higher levels compared to those involved in the adoptive immune response during migration of melanocytes in the embryo on days 3, 3.5, 4, and 4.5 [ 19 ]. We concluded that melanocyte migration negatively regulates immune development in SF embryos, and that the influence continued at the early stage development.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have analyzed the effects of hyperpigmentation in inner organs that affect the development of SF. In our previous work, we found that genes involved in the innate and adoptive immune responses are up and down regulated, respectively, during embryonic development on days 3, 3.5, 4, and 4.5 [ 19 ]. In the present study, we determined the histological distribution of melanocytes and analyzed the populations of immune cells and cytokine gene expression in immune organs during development in SF, White Leghorn (WL), and the hybrid F2 generation birds.…”
Section: Introductionmentioning
confidence: 99%